2015
DOI: 10.1017/s1366728914000881
|View full text |Cite
|
Sign up to set email alerts
|

The use of case marking for predictive processing in second language Japanese

Abstract: Research on processing in English has shown that verb information facilitates predictive processing. Because Japanese verbs occur at the ends of clauses, this information cannot be used to predict the roles of preceding nominals. Kamide, Altmann and Haywood (2003) showed that native Japanese speakers use case markers to predict forthcoming linguistic items. In the present study, we investigated whether second language learners of Japanese demonstrate such predictive effects when processing sentences containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
57
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 78 publications
17
57
3
3
Order By: Relevance
“…Under one widely held view, predictive language processing is implemented by domain-general executive (inhibitory control and working memory) resources. This perspective receives support from numerous studies showing that prediction effects during language comprehension are absent or less pronounced for populations with reduced executive resources, such as children, older individuals, and non-native speakers (e.g., Federmeier et al, 2002;Federmeier & Kutas, 2005;Dagerman, et al, 2006;Federmeier et al, 2010;Mani & Huettig, 2012;Wlotko & Federmeier, 2012;Martin et al, 2013;Kaan, 2014;Mitsugi & Macwhinney, 2016;Gambi et al, 2018;Payne & Federmeier, 2018;cf. Dave et al, 2018;Havron et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Under one widely held view, predictive language processing is implemented by domain-general executive (inhibitory control and working memory) resources. This perspective receives support from numerous studies showing that prediction effects during language comprehension are absent or less pronounced for populations with reduced executive resources, such as children, older individuals, and non-native speakers (e.g., Federmeier et al, 2002;Federmeier & Kutas, 2005;Dagerman, et al, 2006;Federmeier et al, 2010;Mani & Huettig, 2012;Wlotko & Federmeier, 2012;Martin et al, 2013;Kaan, 2014;Mitsugi & Macwhinney, 2016;Gambi et al, 2018;Payne & Federmeier, 2018;cf. Dave et al, 2018;Havron et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Bohnacker & Rosén (2008) meneliti pemrosesan kalimat deklaratif bahasa Jerman sebagai bahasa kedua. Mitsugi & MacWhinney (2015) meneliti pemrosesan penanda pemarkahan dalam bahasa Jepang sebagai bahasa kedua. Pada penelitian Riyanto (1990), bahasa yang diteliti adalah bahasa Belanda dengan penuturnya orang Indonesia yang menguasai bahasa Belanda dan penutur jati bahasa Belanda.…”
Section: Pendahuluanunclassified
“…Menurut Competition Model (CM), ketiga perangkat di atas dapat saling berkompetensi (Mitsugi & MacWhinney, 2015). Petunjuk (cue) yang relatif kuat akan memenangi persaingan sehingga hal tersebut dapat dijadikan cara yang dapat diandalkan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Research on sentence comprehension in adult monolingual speakers has suggested that, in addition to the immediate integration of incoming words into a syntactic structure as a sentence unfolds, predictive processing also takes place, with predictions on incoming information forming even before the information appears in the input [46]. According to this view, sentence processing is “driven by the predictive relationships between verbs, their syntactic arguments, and the realworld contexts in which they occur” [5, p. 247].…”
Section: Introductionmentioning
confidence: 99%